Empowering Youth Leadership: Insights into Sangguniang Kabataan Officials’ Role in Delivering Youth Development Programs and Services - Alphil Christian C. Cabe (Future Science / FSH-PH Publications, 2026)
The Youth Council, which the Filipinos call Sangguniang Kabataan (SK), represents youth in every smallest political unit in the Philippines called a barangay. In the body of research, the youth themselves provide direct insights into how SK delivers as an official government body. However, research on roles and methods for leading youth programs and services in Region XII remains scarce. To fill the existing research gap, the researcher conducted a descriptive study in barangays of a municipality in Region XII, describing the experiences of SK officials in planning, implementing, and evaluating youth development programs and services. The seven participants were purposively selected using the following criteria: be a present SK official in 2023-2024; be at least 23 years old; and have at least 5 years of experience in the SK governance. A semi-structured interview was utilized in collecting the data, and thematic analysis in discovering the main patterns and recurring themes. The findings revealed that SK leaders approach program planning in a deliberate, collaborative, and evidence-based way. Their leadership during implementation shows adaptability, ethical behavior, and systematic operations. The program evaluation process was action-oriented, strategic, and reflective. A conceptual framework was developed, and implications for youth governance, program implementation, and policy development were derived from findings. The study further highlights that youth leadership at the barangay level fosters inclusive, participatory, and sustainable local development, demonstrating that active youth involvement in planning, implementing, and evaluating community programs contributes directly to achieving SDG 11 by strengthening resilient, people-centered, and well-governed human settlements.